2020
DOI: 10.1051/shsconf/20207601013
|View full text |Cite
|
Sign up to set email alerts
|

Fan Ngin Tong Ngin Tjit JongThe Assimilation Face of Grassroot of Chinese Ethnic in Bangka Island, Indonesia

Abstract: Chinese ethnic in Bangka Island has been there since the colonialism and has become part of tin mining history on the island. It is no wonder that the acculturation has stated for a long time ago especially in the grass root society. This study found out how is Chinese assimilation in this area using the qualitative approach. Based on the data from interviews and observations on the field, the writer found out that Chinese assimilation on the island formed a unity identity without losing their own identity. To… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…They measured Bangka-Belitung Province among the top ten (Sumaktoyo, 2021). Earlier studies confirmed the nominating proven by some findings, such as the long story of tolerance among Javanese and Malays (Wati & Buduroh, 2021), smooth assimilation of Chinese ethnic into the local ethnic (Ibrahim et al, 2020), intercultural communication (Mulyana & Zubair, 2015), and hybridity of architecture (Kurniawan et al, 2013). For the multicultural of its people, Futaesaku (2019) nominated Bangka-Belitung Province as a promising cultural tourism destination.…”
Section: Introductionmentioning
confidence: 79%
“…They measured Bangka-Belitung Province among the top ten (Sumaktoyo, 2021). Earlier studies confirmed the nominating proven by some findings, such as the long story of tolerance among Javanese and Malays (Wati & Buduroh, 2021), smooth assimilation of Chinese ethnic into the local ethnic (Ibrahim et al, 2020), intercultural communication (Mulyana & Zubair, 2015), and hybridity of architecture (Kurniawan et al, 2013). For the multicultural of its people, Futaesaku (2019) nominated Bangka-Belitung Province as a promising cultural tourism destination.…”
Section: Introductionmentioning
confidence: 79%
“…The observation results show that the place of residence surrounding or even in the same village as the Malays also determines the occurrence of exogamous marriages between ethnic Chinese and ethnic Malays. This applies to the village context, which does not necessarily apply to life in an urban context (Ibrahim et al, 2017;2019). Examples of villages that show many ethnic Chinese marrying Malays are the Sungai Selan, Lampur, and Trubus areas located in Central Bangka Regency, Pelangas Village, Suntai Hamlet, and Parit Tiga located in West Bangka Regency, Lumut Village and Cengel Hamlet which are located in West Bangka Regency.…”
Section: "I Like Hunting Birds and Squirrels With Malay Friends; Auto...mentioning
confidence: 99%
“…The existence of ethnic Tionghoa who work in tin mining has had a considerable influence on the civilization of the people in Bangka Belitung. The process of exploration and exploitation of tin metal that has been going on for centuries has affected people's lives in various aspects both socially, economically, politically, and culturally [7] , [8], [9]. The arrival of people from outside Bangka and tin mining have formed a cultural system that has developed in Bangka Belitung.…”
Section: Introductionmentioning
confidence: 99%